2017
DOI: 10.1111/ppl.12539
|View full text |Cite
|
Sign up to set email alerts
|

Two Southern Ocean diatoms are more sensitive to ocean acidification and changes in irradiance than the prymnesiophyte Phaeocystis antarctica

Abstract: To better understand the impact of ocean acidification (OA) and changes in light availability on Southern Ocean phytoplankton physiology, we investigated the effects of pCO2 (380 and 800 µatm) in combination with low and high irradiance (20 or 50 and 200 µmol photons m−2 s−1) on growth, particulate organic carbon (POC) fixation and photophysiology in the three ecologically relevant species Chaetoceros debilis, Fragilariopsis kerguelensis and Phaeocystis antarctica. Irrespective of the light scenario, neither g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 58 publications
17
41
1
Order By: Relevance
“…), which was also found for other Antarctic diatom species under these conditions (Trimborn et al. ). To deepen our understanding of OA effects in response to increasing dynamic light, Fragilariopsis curta and Odontella weissflogii were exposed to current and future pCO 2 in combination with moderate and high solar radiation (HSR), applying more realistic climate change scenarios.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…), which was also found for other Antarctic diatom species under these conditions (Trimborn et al. ). To deepen our understanding of OA effects in response to increasing dynamic light, Fragilariopsis curta and Odontella weissflogii were exposed to current and future pCO 2 in combination with moderate and high solar radiation (HSR), applying more realistic climate change scenarios.…”
supporting
confidence: 82%
“…In response to OA, growth and POC production rates were previously reported to decrease in these species under low and medium, but not high constant light (Heiden et al 2016). In response to OA and high irradiance, they further exhibited an increased photosensitivity (Heiden et al 2016), which was also found for other Antarctic diatom species under these conditions (Trimborn et al 2017). To deepen our understanding of OA effects in response to increasing dynamic light, Fragilariopsis curta and Odontella weissflogii were exposed to current and future pCO 2 in combination with moderate and high solar radiation (HSR), applying more realistic climate change scenarios.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…If elevated p CO 2 causes down‐regulation of the CCMs, however, excess light cannot be dissipated as easily and may thus result in photo‐oxidative stress (Rokitta and Rost ; Hoppe et al ). Combined exposure of phytoplankton to elevated p CO 2 and high light indeed showed lowered primary production in natural phytoplankton communities as well as various diatom species (Gao et al ; Trimborn et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Just like the other parameters assessed before, photophysiology was impacted to a much greater degree by Fe limitation than by OA. Trimborn et al (, ) observed no OA‐dependent changes in the photophysiology or pigment composition of P. antarctica when compared to SO diatoms grown under low and elevated irradiances. Similarly, OA also had no effect on the pigment composition and limited impact on the photosynthetic parameters measured in this study.…”
Section: Discussionmentioning
confidence: 98%